Keragaman Dan Kelimpahan Nematoda Secara Horizontal Dan Vertikal Pada Beberapa Tanaman Sayur Di Kabupaten Cianjur - Muhammad Firdaus Oktafiyanto; Roy Ibrahim (Universitas Wiralodra, 2021)
This survey aims to determine the diversity and abundance of nematodes in some plants either horizontally or vertically. Observations horizontally ie by comparing the diversity and abundance of plants nemtoda woetel with different cropping ie monoculture and polyculture. While vertically observations made by comparing the abundance and diversity of nematodes from different soil depths are 0-10, 10-20, and 20-30 in the cabbage and tomatoes. The survey conducted on November 22, 2014, in the village of Sukatani, Cianjur Regency Indonesia. Survey sites located at an altitude of 1,200 meters above sea level, a survey using a zig-zag method, each sample was repeated three times. Laboratory analysis done by extracting the land acquired, and then counting the number of nematode populations obtained under the microscope. Results of the analysis showed there were eleven genus nemtoda obtained by the Rabditis sp., Pratylenchus sp., Helichotilenchus sp., Meloidogyne sp., Rotylenchus sp., Tylenchorynchus sp., Trichodorus sp., Criconemoides sp., Hoplolaimus sp., Dyctilenchus sp., and Monochus sp. spread either horizontally or vertically.